2015
DOI: 10.1177/0284185114530284
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for atlantodental interval in adults and its variation with age and gender in a large series of subjects on multidetector computed tomography

Abstract: ADI measurements on MDCT linearly decrease with increasing age, and these are not affected by gender in adult patients. Different reference values might be used at different ages when diagnosing atlantoaxial anterior dislocation or subluxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
3
18
1
Order By: Relevance
“…Our research contradicts that finding and it could be related to the fact that we looked at a larger series of patients. Similar to other upper cervical anatomical structures, which change with the increasing age, such as the atlantodental interval decreases with increasing age (15), these findings are not unexpected. It might be related to repeated and constant pull, twist, compression forces of the degenerating ligament similar to naturally increasing prevalence of degeneration, such as at the atlantodental joint (16).…”
Section: Discussionsupporting
confidence: 75%
“…Our research contradicts that finding and it could be related to the fact that we looked at a larger series of patients. Similar to other upper cervical anatomical structures, which change with the increasing age, such as the atlantodental interval decreases with increasing age (15), these findings are not unexpected. It might be related to repeated and constant pull, twist, compression forces of the degenerating ligament similar to naturally increasing prevalence of degeneration, such as at the atlantodental joint (16).…”
Section: Discussionsupporting
confidence: 75%
“…In review of literature, a Chinese study on 700 patients reported mean AADI of 1.77 mm with SD of 0.39 mm. 14 The discrepancy in the values could be due to the demographic variation. The difference in the male and female values of AADI were statistically insignificant, which is in agreement with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the male and female values of AADI were statistically insignificant, which is in agreement with other studies. 11,14 We also found AADI levels to reduce as age advances, which was consistent with findings reported by Liu K et al 14 and Osmotherly PG 15 et al Pediatric age group (less than 18 years) has been reported to have a mean ADI of 2.25 mm (SD = 0.24 mm), 16 while we have found the mean AADI to be 1.89 mm (SD = 0.456 mm) in cases less than 20 years of age (►Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,14] Traditionally, C0-C2 relationship has been assessed by measuring of anterior atlanto-dental interval (ADI), posterior atlanto-dental interval (PADI), vertical atlanto-axial index (VAAI), basion-axial interval (BAI) and basion-dens interval (BDI). [1518]…”
Section: Introductionmentioning
confidence: 99%